Correction: Angioarchitectural alterations in the retina and choroid in frontotemporal dementia. - Ariana Allen; Cason B Robbins; Suzanna Joseph; Angela Hemesath; Anita Kundu; Justin P Ma; Alice Haystead; Lauren Winslow; Rupesh Agrawal; Kim G Johnson; Andrea C Bozoki; Sandra S Stinnett; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0312118.].